Pendidikan Perkaderan Gerakan Kepanduan Hizbul Wathan Kafilan Penuntun Moh. Djazman Universitas Muhammadiyah Surakarta Dalam Menyiapkan Kader Militan Muhammadiyah Tahun 2016 - Paresti, Novi; , Dr. Mutohharun Jinan, M. Ag (2016)
ABSTRACT In an organization, cadre and cadre-forming education are very important. Cadre is a driving force of organization and cadre-forming education is an education implanted to the cadres in order that they are ready to do tasks and mandates in future, then, in the organization, they will be the spearhead. Gerakan Kepanduan Hizbul Wathan Kafilah Penuntun Moh. Djazman (The Scout Movement of Hizbul Wathan of Moh. Djazman Guide Contingent) of Muhammadiyah University of Surakarta has a cadre-forming education that keeps on basing on the guidance of the cadre-forming system of Muhammadiyah. In addition, the scout of Hizbul Wathan has the cadre-forming education which is based on Al-Quran and As-Sunnah. This research explained about how the cadre-forming education of the Scout Movement of Hizbul Wathan of Moh. Djazman Guide Contingent of Muhammadiyah University of Surakarta in preparing militant cadres of Muhammadiyah, as well as the supporting factors and the inhibiting factors in implementing the system of the cadre-forming. The method of research which was used in this research was a qualitative research which directly conducting an observation on the field. Previously, observation, documentation, interview, and conclusion taking based on the results which were obtained were conducted. The results of this research revealed that the system of the cadre-forming education used by (The Scout Movement of Hizbul Wathan of Moh. Djazman Guide Contingent) of Muhammadiyah University of Surakarta was able to prepare militant and strong cadres. Nevertheless, during the implementation of the cadre-forming education of Hizbul Wathan Moh. Djazman, several supporting factors were encountered: First, the awareness of all elements on the importance of the implementation of the cadre-forming education. Second, the presence of all elements' willingness in themselves. Third, the presence of all elements' abilities in themselves in conducting the cadre-forming education. Then, the inhibiting factors which inhibited the implementation of the cadre-forming education were: First, the lack of a good communication among the executors of the cadre-forming education. Second, the lack of proffesionalism of the instructors' attitudes in guiding the next-generation cadres. Third, the activities of each individual in their own business. The cadre-forming education which was arranged was then being implemented to the cadres in order that they become the cadres who are militant, strong, and ready to continue the leadership stick in the organization in future after returning to their own region. In this cadre-forming education, Hizbul Wathan Moh. Djazman educated and trained the cadres in order that they are ready and able to implement the goals of Muhammadiyah organization in future. In addition, they are also able to save face of the organization of their umbrella and really struggle hard to complete the mandates.